STUDY OF THE EFFECT OF LOW TEMPERATURES AND CALCIUM CHLORIDE TREATMENT ON THE GERMINATION OF IRANIAN AND EUROPEAN BARLEY CULTIVARS - Abarnak, Setare; Zarei, Leila; Cheghamirza, Kianoosh (Plant Breeding and Seed Science, 2018)
Low temperature stress is one of the limiting factors of seed germination. In order to investigate the effect of low temperatures on germination of barley cultivars, identification of traits related to low temperature stress at germination stage and the effect of calcium chloride on these traits, 44 Iranian and European barley cultivars were evaluated in a factorial experiment within completely randomized design with 3 replications in the Laboratory of Plant Physiology, Agronomy and Plant Breeding department, Razi University. The first factor was 44 Iranian and European barley cultivars, the second factor included four temperature (0, 5, 10 and 20°C), and the third factor was the use of calcium chloride (10 mM) and its non-use (distilled water). Analysis of variance showed that there was a significant difference between cultivars for all traits except root length and seed vigor. Applying calcium chloride treatment at a concentration of 10 mM did not significantly affect the traits under the studied temperatures. Reducing temperature from 20°C to 10°C and 5°C reduced root length, shoot length, coleoptile length, root number, coefficient of velocity of germination, seed vigor and promptness index. The results of correlation analysis showed that there was a significant positive correlation between promptness index with average velocity of germination, coefficient of velocity of germination and seed vigor, germination percentage and root number in all studied temperatures. There was little differentiation between Iranian and European cultivars by both cluster and discriminant analysis.